The Classification of Diffeomorphism Classes of Real Bott Manifolds - Admi Nazra ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2021)
A real Bott manifold (RBM) is obtained as the orbit space of the n-torus T^n by a free action of an elementary abelian 2-group ZZ_2^n. This paper deals with the classification of some particular types of RBMs of dimension n, so that we know the number of diffeomorphism classes in such RBMs.